It Evaluation Moodle sebagai Media Pembelajaran Online pada SMPK Penabur Depok - Chandra Chandra; Syam Gunawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
In order to keep the educational process running smoothly in the face of the COVID-19 pandemic, several schools have turned to online learning platforms. In the context of LMSs, one of the most popular systems is Moodle. Focusing on SMPK PENABUR Depok in the post-COVID-19 era, this study seeks to ascertain the impact of Moodle on the efficacy of learning in educational institutions. The study employs a quantitative methodology to investigate the interrelationships of factors by means of student questionnaires and basic linear regression analysis. With a coefficient of determination of 61.1%, the data demonstrate that Moodle significantly and positively affects the effectiveness of learning. Despite some technological issues, such slow internet, Moodle has improved students' access to course materials, their ability to engage in class discussions, and their level of participation. According to these results, blended learning—which has recently emerged as a viable strategy—can benefit from the use of learning technologies like Moodle to raise the bar for educational excellence. The need of bolstering technological infrastructure and enhancing the quality of online learning platforms to improve the effectiveness of learning going forward is underscored by the implications of this study.